Pemodelan Matriks Kinematika Pada Robot Three-Wheel Swerve Drive: Kinematics Matrix Modeling of a Three-Wheel Swerve Drive Robot - Ilhan Shanjaya, Mohammad Irfan; Endrasmono, Joko; Ahmad Putra, Zindhu Maulana; Sutrisno, Imam; Subiyanto, Lilik; Munadhif, Ii (Jurnal Elektronika dan Otomasi Industri, 2024)
Research in robotics, particularly mobile robots or wheeled mobile robots, continues to grow as their use in various sectors increases to simplify tasks and reduce the risk of human injury. Steering mechanisms, such as Swerve Drive, are becoming an important focus in the development of mobile robots. Swerve Drive enables omnidirectional motion that requires optimal control and complex development. Controlling the Swerve Drive requires large motors and sophisticated algorithms to set the speed and steering angle on each wheel independently, with the aim of achieving the targeted position and orientation. Simulation testing shows that the robot can move well using the prepared kinematics control, with translational, diagonal movement and rotational capabilities as required. Thus, kinematics modeling and development of efficient control algorithms are essential to improve the maneuverability and performance of the swerve drive robot.